Long-Term Retention of Avulsed Maxillary Incisors with Replacement Root Resorption: A 9-Year Follow-Up - Hyunjung Yoon; Minju Song (Hindawi Limited, 2021)
The purpose of this case report is to present a case of long-term retention of avulsed upper maxillary incisors with external replacement root resorption in a 15-year-old boy. The avulsed teeth, #11, 21, and 22, were stored under dry conditions for 40 min and replanted. Endodontic treatment was initiated after two weeks, and the nonrigid splint was removed after 3.5 months. A year after replantation of the teeth, replacement root resorption was detected radiographically. For the following 9 years, the resorption progressed slowly, but the teeth were maintained without any adverse effects on esthetic appearance. Under dry storage conditions, replacement root resorption was expected. In this case, the patient was a growing 15-year-old boy; thus, replantation was performed despite a possible poor prognosis. Consequently, root resorption progressed. Nevertheless, maintenance of the tooth crowns led to satisfying results for the patient both esthetically and psychologically. Ankylosis or replacement root resorption is a complication occurring after replantation of avulsed teeth, which could require additional treatment. However, in young patients, replantation could be considered to maintain the teeth until growth is complete.